Students’ Perceptions of a Gamification in Higher Education - Nyazi, Alaa Khaled (Journal of Educational and Psychological Sciences, 2023)
The goal of the current study is to explore higher education students’ perceptions at Taibah University in Saudi Arabia about integrating a gamification approach into their classes. The descriptive technique was employed by the researcher since it was the most suitable scientific approach. An online survey with 35 questions was distributed to the students via email. The total number of students in the target population was 201. A total of 86 students submitted responses, resulting in a response rate of 43%. The Statistical Package for Social Sciences (SPSS) was used to analyze the data obtained and accomplish the study's objectives. The results showed positive perceptions toward the use of gamification among higher education students at Taibah University. The study also showed that there was a significant difference in integrating the gamification approach between students in the College of Law and the College of Business Administration in favor of Low college.This study recommeneds encourging the faculty members to adopt gamification methods in all their classes to help students easily recall the information and to help them get engaeged with lesson. Further studies need to be conducted to investigate the relationship between students’ personal characteristics (age, gender, and school year) and their perspectives about adopting a gamification approach. The findings of this study indicate that further studies at the colleges of Business Administration need to be conducted to get faculty members and students’ perspectives about adopting a gamification approach.
Keywords: Gamification; students’ perceptions; higher education; Taibah University